Peran Aplikasi Siapik Dalam Meningkatkan Kualitas Laporan Keuangan CV. Rapoviaka Simple - Irma Yanti; Darman Darman; Munawarah Munawarah; Wiri Wirastuti (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research discusses the role of SI APIK application in improving the quality of CV Rapoviaka Simple's financial statements. SI APIK, as an integrated financial information system, is designed to simplify the process of recording, processing, and reporting company finances. The application is designed to simplify the financial recording process, reducing the potential for human error. This study aims to determine the role of the SIAPIK application in improving the quality of financial statements. The type of research used is descriptive qualitative research using primary data. Interviews and observations are a reference in this study to explain a measure of the quality of financial statements. The results of this study indicate that the SI APIK application has succeeded in increasing the efficiency of preparing financial reports. SI APIK also helps in managing financial data in real-time allowing companies to respond to market changes faster.